(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mobile Ad Hoc Networks (MANETs) are decentralized wireless communication systems in which mobile nodes dynamically organize themselves without relying on fixed infrastructure or centralized administration. Their flexibility makes them suitable for military communications, emergency disaster recovery, intelligent transportation systems, wireless sensor deployments, and mobile collaborative environments. However, the absence of centralized control, continuously changing network topology, limited computational resources, and multi-hop communication expose MANETs to numerous routing attacks including black hole attacks, wormhole attacks, Sybil attacks, route fabrication, packet dropping, replay attacks, and malicious node impersonation. Traditional cryptographic routing protocols improve authentication and confidentiality but remain vulnerable to distributed trust management challenges because they rely on centralized certificate authorities or static trust assumptions. This study proposes a Blockchain-Based Secure Routing Framework for Mobile Ad Hoc Networks (BSRF-MANET) that integrates blockchain-based distributed trust management with secure route discovery, node authentication, cryptographic verification, malicious node identification, and secure packet forwarding. The proposed framework consists of node registration, distributed identity verification, blockchain ledger maintenance, route validation, trust computation, secure path selection, and routing performance evaluation. The framework aims to reduce routing attacks while improving packet delivery ratio, network throughput, route reliability, authentication integrity, and overall network resilience.